Understanding of stoichiometry by learners from Form Four to final year of general secondary education in Cameroon - Ateba, Jeremie Awomo; Woukeng, Josephine Nita Tematio; Nchia, Lawrence Ntam; Bouni, Ayina (European Scientific Journal, ESJ, 2025)
The aim of the present research is to determine the conceptions of learners from Form Four to upper sixth (13-19 years) of general secondary education in Cameroon about the concept of stoichiometry. A preliminary analysis of the didactic transposition of the concept of chemical reaction in the Form Four textbook, combined with an epistemological study of the concept of stoichiometry, enabled us to design an 8-item paper-and-pencil questionnaire. The questionnaire was administered to 239 learners from four to Upper Sixth students of five general secondary schools. The data collected were analyzed using Dehon’s (2018) significance level model. The results show that many learners attribute irrelevant meanings to the concepts of the stoichiometry conceptual network. These meanings are mainly at the symbolic meaning level. In this article, we hope to provide teachers with starting points for better teaching of the integrative concept of stoichiometry. Thus, teachers should insist on the constant composition of molecules when teaching chemical reactions.